2017
DOI: 10.1016/j.shaw.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of the Lighting at the Entrance of a Very Long Road Tunnel: A Case Study in Ilam

Abstract: BackgroundAt the entrance of a tunnel, reflection of sunlight from the surrounding environment and a lack of adequate lighting usually cause some vision problems. The purpose of this study was to perform a safety evaluation of lighting on a very long road in Ilam, Iran.MethodsThe average luminance was measured using a luminance meter (model S3; Hagner, Solna, Sweden). A camera (model 108, 35-mm single-lens reflex; Yashica, Nagano, Japan) was used to take photographs of the safe stopping distance from the tunne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 16 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…9 , 19 Safe stopping distance depends on several factors, including road gradient (upward or downward; ± s , %), passing vehicle speed limit ( U , m/s), driver reaction time ( t 0, s), acceleration due to gravity ( g , m/s 2 ), and the coefficient of friction between the tire and the road ( f , dimensionless). 1 Eq. 2 is used to calculate the SSD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…9 , 19 Safe stopping distance depends on several factors, including road gradient (upward or downward; ± s , %), passing vehicle speed limit ( U , m/s), driver reaction time ( t 0, s), acceleration due to gravity ( g , m/s 2 ), and the coefficient of friction between the tire and the road ( f , dimensionless). 1 Eq. 2 is used to calculate the SSD.…”
Section: Methodsmentioning
confidence: 99%
“…Road traffic accidents that occur in tunnels make up a small percentage of road accidents, but with enormous consequences. 1 , 2 In the meantime, the accident rate in the entrance zone of tunnel is so high compared to other areas; such that the Norway Highway Bureau reported that about 63.7% of tunnel collisions occur at entrance zones. 2 Many studies have suggested that the visual features for drivers approaching a tunnel entrance are crucial factors to assess the risk of crash related to tunnel travel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate lighting will make the employees produce more products with less error, leading to a 10–50% increase in productivity and efficiency of the employees [ 17 ]. Therefore, undesirable environmental conditions such as exposure to inappropriate heat and light will influence human error, the occurrence of accidents, and productivity level through the adverse effect on cognitive performance such as attention, concentration, and reaction time [ 11 , 18 ].…”
Section: Introductionmentioning
confidence: 99%